2013
DOI: 10.5657/fas.2013.0137
|View full text |Cite
|
Sign up to set email alerts
|

Variation and Profile of Paralytic Shellfish Poisoning Toxins in Jinhae Bay, Korea

Abstract: To understand critical aspects of paralytic shellfish poisoning (PSP) in a chief area of bivalve production in Korea, seasonal variation in PSP toxins in bivalves collected from Jinhae Bay, Korea in 2009 was surveyed by the pre-column high-performance liquid chromatography oxidation method. We also confirmed the profiles of major bivalves such as oysters Crassostrea gigas and mussels Mytilus galloprovincialis in Jinhae Bay. PSP toxins in the bivalves showed remarkable seasonal variation. PSP toxin levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Statistical analysis demonstrated that sxtA4 expression was correlated with STXs eq in low temperature and cold shock samples, whereas sxtG was sensitive to temperature changes. These results were in accordance with the results of field monitoring data, i.e., most PST contamination of shellfish by A. catenella occurred in spring and autumn (8.2–15 °C) in Korean coasts [ 89 ]. In addition, resting cysts of the Alexandrium spp.…”
Section: Discussionsupporting
confidence: 89%
“…Statistical analysis demonstrated that sxtA4 expression was correlated with STXs eq in low temperature and cold shock samples, whereas sxtG was sensitive to temperature changes. These results were in accordance with the results of field monitoring data, i.e., most PST contamination of shellfish by A. catenella occurred in spring and autumn (8.2–15 °C) in Korean coasts [ 89 ]. In addition, resting cysts of the Alexandrium spp.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, Gyeongnam province, located in the south of Korea, produced the largest amount of oysters in Korea, accounting for~90% of oyster products. The products are consumed domestically or exported, mainly to the United States (US), Japan, and the European Union (EU) (Mok et al, 2013(Mok et al, , 2014a(Mok et al, , 2015. The Korean government has established a memorandum of understanding with the US and EU, and there are designated shellfish growing areas for export along the southern coast of Korea which meet the standards set by these countries (Mok et al, 2014a(Mok et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The vessel was covered and left overnight at ince, has been the designated shellfish-cultivation area for export since 2009 because it is an important mussel-cultivation area in Korea (Ha et al, 2013). The products are consumed domestically or exported mainly to the EU (Mok et al, 2013). Therefore, the safety of Korean seafood is very important to Korea and importing countries, including the EU.…”
Section: Sample Preparationmentioning
confidence: 99%